Beginner's Iraqi Arabic an introduction to the spoken language of Iraq - Nasrallah, Nawal; Hassani, Nadia (Beginner's guides (New York, N.Y.), 2006)
Presents an introduction to the spoken language of Iraq. This work is designed both for people with no previous knowledge of the Arabic language and those who know some Arabic and wish to learn the Iraqi dialect. It contains Arabic words which are transliterated into Roman script for easy understanding